Karakterisasi DNA Gen Beta Globin Berdasarkan Konsentrasi dan Kemurniannya Pada Talasemia β Minor - Novilla, Arina; Romlah, Sitti; Khristian, Erick; Sari, Jesica Putri Puspita (Universitas Mohammad Husni Thamrin, 2025)
Thalassemia minor is a heterozygous condition caused by a mutation in the β-globin gene, which results in a decrease in β-globin chain synthesis without severe clinical symptoms. Identification of mutations in the β-globin gene through DNA analysis is the main approach in the enforcement of the molecular diagnosis of thalassemia minor. The success of such analyses is greatly influenced by the concentration and purity of the DNA, as low-quality DNA can inhibit PCR amplification and decrease the accuracy of mutation detection. Therefore, the DNA characterization of β genes accompanied by evaluation of DNA concentration and purity due to DNA quality directly affects the success of molecular analyses such as PCR and DNA sequencing. The method of this study is an experiment, DNA Isolation using the Geneaid gSYNCTM DNA Extraction kit. The results of the DNA isolation process were then qualitatively examined using electrophoresis of a concentration of 1% on agarose gel. Based on the results, it can be concluded that the purity value in the range of 1.2-1.8, as many as 5 samples of purity is not good and 1 sample of purity is good, because the purity value of good DNA is 1.8-2.0. The results of DNA concentration were in the range of 18.6-41.5 ng/ul, as many as 1 sample of inadequate DNA concentration and 5 samples of adequate DNA concentration because the adequate DNA concentration was in the range of 20–100 ng/μL. Keywords: Beta globin gene, Concentration, Purity, Thalassemia β minor